Evaluation of the Anti-fouling Efficacy of Bacillus licheniformis Extracts Under Environmental and Natural Conditions - Muras, Andrea; Larroze, Severine; Mayer, Celia; Teixeira, Tânia; Wengier, Reut; Benayahu, Yehuda; Otero, Ana (Frontiers in Marine Science, 2021)
There is an increasing interest in developing innovative coatings and testing natural products with anti-fouling activity to substitute current highly toxic biocides that have a harmful impact on marine organisms. Bacillus licheniformis species have shown different anti-biofilm and anti-fouling activities in vitro, but so far, its efficacy in field trials has not been tested. For this purpose, the capacity of different extracts of B. licheniformis NCTC 10341T to prevent micro and macro-fouling was first tested in vitro. The methanol cell extract (MCE) inhibited bacterial biofilm formation without significantly affecting planktonic growth and displayed a significant efficacy to prevent larval settlement of the macro-fouler Bugula neritina in vitro without inducing lethality. Additionally, the MCE presented low toxicity against the non-target species Artemia salina. The B. licheniformis MCE was then incorporated in a self-polishing paint at 2 and 5% w/w and tested in a static immersion experiment in the Gulf of Aqaba (northern Red Sea) for 180 days. Fouling coverage decreased by 30% in the 5% MCE-treated panels in comparison with the control panels. Differences in the anti-biofilm activity of the extracts depending on the culture medium highlight the importance of the strict control of culture conditions for the production of biomass with stable bioactive activity. The results indicate the potential of B. licheniformis NCTC 10341T crude extracts for environmentally friendly anti-fouling applications, although a deeper characterization of the bioactive compounds present in the B. licheniformis MCE and its mode of action is required to allow strict control of the activity of the extracts to achieve large-scale industrial production.